Peningkatan Pemahaman Mahasiswa Tentang Proses Lupa Dan Transfer Pembelajaran Melalui Strategi Diskusi Reflektif - Siti Hanifah Parawansah; Mahmud Yunus; M Rizqil Hasan Muqorrobin; Nurul Qomariyah; Syamsuddin Syamsuddin; Sholehatul Muarrifah; Miftahul Hasan; Moh Hasan Firghol Muttaqien (Universitas Cokroaminoto Yogyakarta, 2025)
This study investigates the use of reflective discussion strategies to improve students’ understanding of forgetting and learning transfer. Conducted as Classroom Action Research on second-semester students of the Islamic Education Management Program at Zainul Hasan University, the study followed the stages of planning, implementation, observation, and reflection. Data from observations, interviews, and documentation were analyzed through data condensation. Results show that reflective discussions enhanced students’ grasp of forgetting theories and learning transfer types, while increasing their metacognitive awareness. The strategy proved effective in deepening conceptual understanding within the context of higher education learning.